Microwave-Based Technique For Glucose Detection - Md Salim, Nora Salina (2010)
Glucose biosensor is generally based on reaction between glucose and enzyme glucose oxidase (GOD) that produces gluconic acid and hydrogen peroxide. The gluconic acid is a conducting medium while hydrogen peroxide is a polar molecule. This work discovers the changes of dielectric properties due to conductive loss below 4 GHz and dipole orientation of above 4 GHz of this reaction. The difference between the dielectric properties of an enzyme and glucose-enzyme reaction can be related to the glucose concentration in the sample. The dielectric properties of glucose solutions, enzyme GOD and glucose-enzyme reaction were measured using the Open Ended Coaxial Probe with frequency range from 200 MHz to 20 GHz at room temperature (25 'C). Two types of juice are used in this study; blackcurrant juice and lychee juice. The actual glucose content in juice samples were analyzed using High Performance Liquid Chromatography method. This technique has also been applied using the microstrip sensor for measuring glucose concentration in glucose solution, blackcurrant juice and lychee juice. The result shows that the highest sensitivity for the differences in dielectric changes with glucose concentrations due to the effect of ionic conductivity and dipole orientation were found at 0.99 GHz and 16.44 GHz respectively. The changes in dielectric loss are preferable for derivation of glucose concentration. In this proposed technique, the detection limit of glucose concentration is as low as 0.01 M (0.20 g/100 ml) with optimum ratio of 1:3 for an enzyme and glucose. Lychee juice has a higher dielectric loss difference for both frequencies followed by blackcurrant juice and glucose solution due to the contribution of free ions in the juice. The sensitivity of attenuation measurement using microstrip sensor is dependent on the dielectric loss of materials. The sensitivity of measurement about 0.002 dB/ (mg/ml) at 0.99 GHz and 0.004 dB/ (mg/ml) at 16.44 GHz which are comparable to the current microwave techniques. This technique gives benefit to the future development of microwave biosensor by which both ionic conductivity and dipole effects are occurred simultaneously.